Relationship between parental participation and adolescents’ academic success in Nadia and Jalpaiguri districts (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
The present study investigated the relationship between parents' participation in their children's education and academic success in the post-pandemic period. A cross-sectional survey design was used, and 209 respondents were selected through a simple random sampling technique. The results revealed that parental involvement has a negative correlation (p>0.05) with their children's academic success but not significantly affecting the same. Apart from that, some other social and educational attributes of the children also contributed to their academic success to a great extent. Further research is needed to explore other potential factors that may contribute to academic success in children.